Respuesta :

Answer:

C

Step-by-step explanation:

f(x) = 2(3)^x - 6            find the x and the y intercept

                                   x intercept is when y = 0

                                   y intercept is when x = 0

f(x) = 2(3)^x - 6       x=0

f(0) = 2(3)^0 - 6

     = 2(1)  - 6

f(0) = 2 - 6         y = -4       (0, -4) is the y intercept

f(x) = 2(3)^x - 6  = 0      now y or if you perfer f(x) is equal to 0

        2(3)^x = 6            substracted 6 from both sides  

        (3)^x = 6/2           divided both sides by 2

        (3)^x = 3              when x = 1     3 = 3

              x = 1         (1, 0) is the x intercept  

ACCESS MORE